First record of some fishes from Libyan waters - Al Hassan, L A J (Indian Journal of Fisheries, 2011)
The Libyan coast of the Mediterranean is about 1,500 km including the bathymetricalareas and closely associated with the major structural features of theAfrican continent. The hydrological conditions of the region are dominated bythe presence of three layers of water masses: the surface, the intermediateand the deep layer. Water temperature range from 23Â°C to 24Â°C.